Análise do efeito da liderança sobre a cultura organizacional das agências do INSS da região administrativa de Araraquara/SP - Somenzari, Marcel Sigrist (2018)
The present research discusses the relations between leadership and organizational culture in the Brazilian public sector. The objective of the study was evaluate the effect of leadership on the organizational culture of thirteen agencies of the Instituto Nacional do Seguro Social (INSS) of the Araraquara administrative region, located in the interior of the State of São Paulo. The work was carried out through a survey, namely, a data collection for the accomplishment of a correlational study. For this purpose, two models of survey questionnaires for quantitative analysis were used: the Multifactor Leadership Questionnaire, developed by Bass and Avolio (1990), and the Competing Values Framework, produced by Cameron and Quinn (2006). The assertions of the questionnaires were adapted to the 5-point Likert scale. The questionnaires were applied to the organizational individuals of the agencies under study, obtaining a valid sample of 166 respondents, being 13 managers and 153 employees of the agencies teams surveyed. For the treatment of the data collected in the survey, descriptive and exploratory analyzes were carried out, using the partial least squares approach of the structural equation modeling method (HAIR; RINGLE; SARSTEDT, 2011). It was possible to validate the relationships identified between the leadership and organizational culture constructs in the INSS agencies of the Araraquara administrative region. The results demonstrate the predominance of the transformational leadership style (BURNS, 1978; BASS; AVOLIO, 1993) and the type of clan culture (CAMERON; QUINN, 2006), as well as the correlation between these two constructs as the one that most stood out among the several correlations present between leadership and organizational culture in the INSS agencies surveyed. Finally, it was possible to conclude that, in the perception of the respondents, leadership influences the culture of a public organization, through a positive correlation of high statistical significance (COHEN, 1992).